2021
DOI: 10.1088/1742-6596/1825/1/012030
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of Concentration and Wavelength Dependent Refractive Index of Sugar Solution Using Sellmeier Equation

Abstract: The concentration and wavelength-dependent refractive index of sugar solution have been determined using Sellmeier Equation. The equations describe the refractive index as a function of wavelength parameter. They could be generalized as a function of material concentration by investigating the characteristic of their Sellmeier constants A and B. The three wavelengths used to identify the refractive index of sugar solutions were 455 nm, 525 nm, and 633 nm, while the concentration of the sugar solution ranged fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…[1] Misto et al [2] and compares them to the linear fits obtained in this work for the dependence of the refractive index on concentration. Fig.…”
Section: Literature Comparisonmentioning
confidence: 82%
See 2 more Smart Citations
“…[1] Misto et al [2] and compares them to the linear fits obtained in this work for the dependence of the refractive index on concentration. Fig.…”
Section: Literature Comparisonmentioning
confidence: 82%
“…Again, the lowest value measured by Tan et al [1] was at 1 w%. For Misto et al [2] we added a linear offset and again have a great overlap with the slopes. Misto et al [2] also showed the dependence on the measurement wavelength λ.…”
Section: Literature Comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…: glucose) or salt concentration in water or water-based solutions (e.g. : blood) [8], [9], to distinguish water-based solutions and some other liquids [10], monitor haemoglobin and blood [11], [12], several protein and DNA solutions [13]- [16].…”
Section: Introductionmentioning
confidence: 99%
“…When the PCF's phase-matching requirement between the fundamental and surface plasmon-polariton (SPP) modes is met, the SPR is frequently employed in optical fiber detection [15]. To advance PCF sensing technology, several SPR-based PCF refractive index sensor types have been investigated within the last 20 years [12][13][14][15][16][17][18]. The detection of biological and biomolecular analytes [4], bioengineering [9], biochemistry [6], and bioimaging [17] are only a few applications for the SPR phenomenon.…”
Section: Introductionmentioning
confidence: 99%